STUDI PEMANFAATAN FASILITAS POKOK PANGKALAN PENDARATAN IKAN TIKU KABUPATEN AGAM PROVINSI SUMATERA BARAT - Amalia, Etika; Syaifuddin, Syaifuddin; Zain, Jonny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted in PPI Tiku Agam, West Sumatra Province in January 2018 with survey method. This research was conducted to obtain information about the on the type, condition, existence, and capacity of basic facility of Fish Landing Base (PPI) Tiku Agam District, West Sumatra Province. All information is useful to know the condition and the level of utilization of basic facilities in PPI Tiku. From the technical calculation, the utilization rate of the facility shows that the land utilization rate is 10.24% with the total land area of PPI Tiku is 2.89 ha. The utilization rate of dock facilities is 0% with a dock length of 150 m wide 8 m of closed construction and is jetty type jetty. The utilization rate of depth of harbor pool is 100 % with area of 5 ha and depth of pond is needed that is 1,89 m and to the unused pond 1.30 m.Keywords : PPI Tiku, basic facility, study of utilization of facility